By launch to Indonesian isles missionary work in the Rhio Archipelago - Finlay, Matthew H. (London, UK Pickering and Inglis, 1954)
Includes photographs.
Brethren writer. This copy signed by author. Mr and Mrs M.H. Finlay were commended from assemblies in Tauranga and Te Puke (New Zealand) in 1946.
Keywords: Brethren movement -- missionaries -- Indonesia